Steps to construct educational interventions on sexual dysfunction for healthcare professionals and patients. Experiences from the SECRET research study-group - Rikke Meyer; Sita R. Kotnis; Cecilie M.Ø. Fog-Petersen; Lise Tarnow; Annamaria Giraldi; Gesche Jürgens; Charlotte B. Jacobsen (PEC Innovation)
Objectives: To design an educational intervention on sexual dysfunction for patients suffering from schizophrenia and diabetes based on patients' and other relevant stakeholders' preferences, and to offer transparency into the basic decision-making process behind a final design. Methods: We conducted a three-part investigation to explore theory, preferences, and feasibility based on literature searches and interviews with patients, healthcare professionals, heads of Assertive Community Treatment Centres and experts. Based on a content analysis of this material, a draft of the intervention was developed. The draft was quality-checked by involvement of stakeholder representatives and refined to its final design. Results: The intervention evolved into having two components: One intervention for patients and one for healthcare professionals. In patient education, meeting peers and predictability were important factors. For healthcare professionals, daily clinical activities were prioritised. Conclusions: We present a framework for an educational intervention about sexual dysfunction, schizophrenia and diabetes targeting both patients and healthcare professionals. Innovation: The transparency of the design process underlying the interventions allows for reproduction and eases further refinement, extension, and adjustment if implemented in other contexts.